Performance factors of Kopitiams in Kota Kinabalu, Sabah - Wong, Wai Yew (2007)
This research aims to determine sales perrormance factors for coffee shop or better known as Kopitiam operating in Kota Kinabalu, Sabah. The objective is achieved by analyzing relationships between sales of Kopitiams against the factors stipulated in the proposed model. The model consists of two theories with two factors each and a marketing strategy with four factors. The first theory is human capital theory which consists of the education and experience factors. The second theory is organizational theory which consists of size and age factors. As for the marketing strategy it consists of price, promotion, place and product factors. Questionnaires data were collected from 93 Kopitiams in Kota Kinabalu. Results from analysis reveal that 36.2% of the variances are able to be explained by the model, with education, age, size and place strategy significant. It is hope that, this research has contributed to researches in this field at the micros, small and medium enterprise level and can use by future researcher as a reference to develop a better model.